Challenges and Opportunities of Choosing a Membrane for Electrochemical CO2 Reduction - Helene Rehberger; Mohammad Rezaei; Abdalaziz Aljabour (Membranes)
The urgent need to reduce greenhouse gas emissions, particularly carbon dioxide (CO2), has led to intensive research into novel techniques for synthesizing valuable chemicals that address climate change. One technique that is becoming increasingly important is the electrochemical reduction of CO2 to produce carbon monoxide (CO), an important feedstock for various industrial processes. This comprehensive review examines the latest developments in CO2 electroreduction, focusing on mechanisms, catalysts, reaction pathways, and optimization strategies to enhance CO production efficiency. A particular emphasis is placed on the role of ion exchange membranes, including cation exchange membranes (CEMs), anion exchange membranes (AEMs), and bipolar membranes (BPMs). The review explores their advantages, disadvantages, and the current challenges associated with their implementation in CO2 electroreduction systems. Through careful analysis of the current literature, this report aims to provide a comprehensive understanding of state-of-the-art methods and their potential impact on sustainable CO production, with a special focus on membrane technologies.